Subsidizing human capital to overcome the green paradox: A demand-side approach - Arne Steinkraus (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2016)
This paper shifts the perspective of the recent green paradox literature towards the demand side. Based on a simple model, I show that a subsidy on input factors in a Cobb-Douglas production function may contribute substantially to postponing resource extraction into the future and, thereby, to limit the future costs of climate change. Specifically, indirect subsidies on human capital, such as investments in education, are plausible policy options to mitigate carbon dioxide emissions because it is robust to short-sighted incentives on the part of politicians and resource owners.
Keywords: Q38; Q54; Q58; 330; Climate Change; Green Paradox; Subsidy; Demand-Side